Architectural and circuit model of GNSS+INS navigation device - Karibayev, Б.А.; Meirambekuly, Н.; N.Sh. , Н.Ш. (Recent Contributions to Physics, 2024)
The work is devoted to the creation of a prototype of a navigation module intended for a civil scientific rocket. The study covers the design process, from the selection of hardware components to the development of electrical circuits and modular architecture of the device. The project is based on the integration of the global navigation satellite system (GNSS) and the inertial navigation system (INS), which allows achieving high accuracy in determining the coordinates and parameters of the rocket's motion in real time. The module architecture is based on the use of the STM32F777VI microcontroller, which provides data processing, control of peripheral devices and integration with the UM980 GNSS module and the LSM6DSV32X inertial sensor. The system is supplemented with an E22-400T33S radio module for telemetry transmission, LED indication and communication interfaces such as UART and SPI. For stable operation, the use of step-down power converters, a quartz generator and protective elements against electrostatic discharges are provided. The developed model allows studying the functionality of the system, testing innovative approaches in rocket engineering and conducting scientific experiments at altitudes of up to 50 km. The presented work is the basis for further stages – calibration, field testing and adaptation to specific operating conditions.